1999
DOI: 10.1038/19709
|View full text |Cite|
|
Sign up to set email alerts
|

The CED-4-homologous protein FLASH is involved in Fas-mediated activation of caspase-8 during apoptosis

Abstract: Fas is a cell-surface receptor molecule that relays apoptotic (cell death) signals into cells. When Fas is activated by binding of its ligand, the proteolytic protein caspase-8 is recruited to a signalling complex known as DISC by binding to a Fas-associated adapter protein. A large new protein, FLASH, has now been identified by cloning of its complementary DNA. This protein contains a motif with oligomerizing activity whose sequence is similar to that of the Caenorhabditis elegans protein CED-4, and another d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
189
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(196 citation statements)
references
References 47 publications
5
189
1
1
Order By: Relevance
“…Recently, we have identified a novel protein, FLASH, with binding activity to Casp8NC-DED through its DED-recruiting domain (DRD), which is involved in Fas-mediated activation of caspase-8 during apoptosis (Imai et al 1999). We have also observed that Cooperative effects of two repeated DEDs for apoptosis FLASH is included not only in Fas-induced deathinducing signalling complex (DISC) which contains Fas, FADD and caspase-8 during Fas-mediated apoptosis, but also in Casp8NC-DED-induced DEF (Y.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have identified a novel protein, FLASH, with binding activity to Casp8NC-DED through its DED-recruiting domain (DRD), which is involved in Fas-mediated activation of caspase-8 during apoptosis (Imai et al 1999). We have also observed that Cooperative effects of two repeated DEDs for apoptosis FLASH is included not only in Fas-induced deathinducing signalling complex (DISC) which contains Fas, FADD and caspase-8 during Fas-mediated apoptosis, but also in Casp8NC-DED-induced DEF (Y.…”
Section: Discussionmentioning
confidence: 99%
“…1 Among the two well-defined apoptotic pathways, receptor-mediated apoptosis is characterized by the formation of the deathinducing signaling complex (DISC). 2 On the other hand, chemical-induced apoptosis generally leads to mitochondrial damage resulting in the release of cytochrome c that associates with Apaf-1, caspase-9 and dATP to form a multiprotein complex called apoptosome. 3 The DISC and apoptosome complex activate procaspase-8 and -9, respectively.…”
mentioning
confidence: 99%
“…Component of the apoptosis signaling pathway required for the activation of CASP8 in Fasmediated apoptosis (Imai Y et al, 1999). Component of the machinery required for histone precursor mRNA expression and essential for 3end maturation of histone mRNAs (Barcaroli D et al, 2006;De Cola et al, 2012;Yang XC et al, 2009).…”
Section: Functionmentioning
confidence: 99%